2020
DOI: 10.1093/cid/ciaa1036
|View full text |Cite
|
Sign up to set email alerts
|

Sparganosis (Spirometra) in Europe in the Molecular Era

Abstract: Sparganosis is a relatively neglected food- and waterborne disease caused by species of the tapeworm genus Spirometra the global distribution of which has not been sufficiently recognised. Known mainly as a zoonosis of East Asia, its species are native to all inhabited continents including Europe. Spirometra has been reported from numerous wildlife species from 17 European countries and a critical review confirmed 17 autochthonous and 8 imported human clinical cases. We present the first molecular evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
107
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(116 citation statements)
references
References 23 publications
1
107
0
8
Order By: Relevance
“…To clarify the phylogenetic relationship of the enigmatic parasite S. proliferum with other cestode species and investigate the underlying pathogenic mechanisms, we sequenced its entire genome as well as that of newly isolated S. erinaceieuropaei (it should be noted that recent studies suggested that Asian S. erinaceieuropaei can be taxonomically distinguished from European S. erinaceieuropaei 15,16 , but we retain the name S. erinaceieuropaei for the Japanese isolate). We also performed transcriptome analyses of S. proliferum plerocercoid larvae to identify genes that are involved in asexual proliferation in the host.…”
mentioning
confidence: 99%
“…To clarify the phylogenetic relationship of the enigmatic parasite S. proliferum with other cestode species and investigate the underlying pathogenic mechanisms, we sequenced its entire genome as well as that of newly isolated S. erinaceieuropaei (it should be noted that recent studies suggested that Asian S. erinaceieuropaei can be taxonomically distinguished from European S. erinaceieuropaei 15,16 , but we retain the name S. erinaceieuropaei for the Japanese isolate). We also performed transcriptome analyses of S. proliferum plerocercoid larvae to identify genes that are involved in asexual proliferation in the host.…”
mentioning
confidence: 99%
“…Sparganosis is a globally distributed neglected water- and food-borne disease caused by larval stages of Spirometra sp. located in various human body tissues [ 34 ]. The occurrence of Spirometra infections across South America has been reported since the beginning of the 20th century [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, Almeida et al [8] report the occurrence of at least two species of Spirometra in South America, which are different from Old World taxa. In the most recent reports [5,9], American Spirometra species are split into two S. decipiens complexes.…”
Section: Discussionmentioning
confidence: 99%
“…that prey on the intermediate or paratenic hosts. In humans, the disease produced by the development of the Spirometra's plerocercoids is known as sparganosis [4,5]. In rare cases, the adult stage of Spirometra spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation